Assessment of peripapillary retinal nerve fiber layer thickness using scanning laser polarimetry (GDx VCC) in normal Indian children - Mayuri B Khamar; Vaishali Vasavada; Sajani K Shah; Rupal H Trivedi; Ravi Thomas (Indian Journal of Ophthalmology, 2013)
Purpose: To obtain reference values of RNFL thickness in normal Indian children and to study the association of RNFL thickness with central corneal thickness(CCT) and axial length(AL). Materials and Methods: 200 normal Indian children (mean age 8.6 ± 2.9 yrs) were examined on the GDxVCC. The inferior average (IA), superior average (SA), temporal-superior-nasal-inferior-temporal (TSNIT) average and nerve fiber index (NFI) values were recorded and compared between males and females as well as between the different age groups. The association of TSNIT average with AL and CCT was examined. Results: Values for the RNFL parameters were-SA: 64.9 ± 9.7, IA: 63.8 ± 8.8, TSNIT average: 53.5 ± 7.7 and NFI 21.5 ± 10.8. Superior, inferior and TSNIT averages did not differ significantly between males and females (P = 0.25, P = 0.19, P = 0.06 respectively; Mann-Whitney U test). No significant differences were found in TSNIT average across age groups. There was a statistically significant positive correlation between CCT and TSNIT average (r = 0.25, r 2 = 0.06, P < 0.001). The correlation TSNIT average and AL(r = −0.12; r2 = 0.01) was not significant (P = 0.2). Conclusion: Reference values for RNFL parameters reported for Indian children are similar those reported in adults. There is a small correlation between central corneal thickness and RNFL as reflected in average TSNIT.